Pengelolaan Pembiayaan Pendidikan Di Madrasah Ibtidaiyah Swasta Piladang, Kabupaten Lima Puluh Kota, Sumatera Barat - Silvia Marlina; Junaidi Junaidi (Thawalib: Jurnal Kependidikan Islam, 2023)
The aim of the study was to analyze and describe the educational financing management model in Piladang Private Madrasah Ibtidiiyah. Qualitative research methods with a case study approach. The first data collection technique was interviewing 1 school principal, 1 vice principal, 1 finance staff, 1 administrative staff, 2 teachers, and 2 students; second run; and third observation. Data processing techniques with reduction, data presentation, and conclusion. Data validation technique with technique and source triangulation. The results of the study show: (1) financing planning by planning the costs of admitting new students, educational development, and community contributions. (2) use of costs for infrastructure, salaries of teaching and educational staff, office stationery, and other madrasah operations. (3) financing supervision: firstly by the Foundation by checking the school's account, secondly by the school principal by checking proof of school financial expenses. (4) reporting and accountability by making madrasah financial reports which are reported to school principals and foundations every semester.